Current trends in the management of extra-abdominal desmoid tumours - Papagelopoulos, Panayiotis J (BioMed Central, 2006)
Extra-abdominal desmoid tumours are slow-growing, histologically benign tumours of fibroblastic origin with variable biologic behaviour. They are locally aggressive and invasive to surrounding anatomic structures. Magnetic resonance imaging is the modality of choice for the diagnosis and the evaluation of the tumours. Current management of desmoids involves a multidisciplinary approach. Wide margin surgical resection remains the main treatment modality for local control of the tumour. Amputation should not be the initial treatment, and function-preserving procedures should be the primary treatment goal. Adjuvant radiation therapy is recommended both for primary and recurrent lesions. Chemotherapy may be used for recurrent or unresectable disease. Overall local recurrence rates vary and depend on patient's age, tumour location and margins at resection.